Actinobaculum schaalii an emerging pediatric pathogen? - Zimmermann Petra; Berlinger Livia; Liniger Benjamin; Grunt Sebastian; Agyeman Philipp; Ritz Nicole (BMC Infectious Diseases, 2012)
Abstract Background Actinobaculum schaalii was first described as a causative agent for human infection in 1997. Since then it has mainly been reported causing urinary tract infections (UTI) in elderly individuals with underlying urological diseases. Isolation and identification is challenging and often needs molecular techniques. A. schaalii is increasingly reported as a cause of infection in humans, however data in children is very limited. Case presentation We present the case of an 8-month-old Caucasian boy suffering from myelomeningocele and neurogenic bladder who presented with a UTI. An ultrasound of the urinary tract was unremarkable. Urinalysis and microscopy showed an elevated leukocyte esterase test, pyuria and a high number of bacteria. Empiric treatment with oral co-trimoxazole was started. Growth of small colonies of Gram-positive rods was observed after 48 h. Sequencing of the 16S rRNA gene confirmed an A. schaalii infection 9 days later. Treatment was changed to oral amoxicillin for 14 days. On follow-up urinalysis was normal and urine cultures were negative. Conclusions A.schaalii is an emerging pathogen in adults and children. Colonization and subsequent infection seem to be influenced by the age of the patient. In young children with high suspicion of UTI who use diapers or in children who have known abnormalities of their urogenital tract, infection with A. schaalii should be considered and empiric antimicrobial therapy chosen accordingly.